Prevalence of Post-Tonsillectomy Hemorrhage in Adults and Children - Mohammad Hosein Taziki; Mehran Hosseini; Hoseini Fazli; Sepideh Sadat Hosseini (Golestan University Of Medical Sciences, 2020)
Background and objectives: Hemorrhage is the most common complication of tonsillectomy. However, the incidence of post-tonsillectomy hemorrhage may be affected by various factors including weight, age, medications, surgical technique, etc. This study was carried out to determine prevalence of post-tonsillectomy hemorrhage in patients undergoing tonsillectomy in a teaching hospital in Gorgan, Iran. Methods: This descriptive study was conducted on 1,043 cases of tonsillectomy who were admitted to a referral teaching hospital in Gorgan (Iran) between 2016 and 2017. Data were collected from medical records. Demographics characteristics, the applied surgical technique (e.g., tonsillectomy, adenoidectomy and adenotonsillectomy), the time of bleeding onset, the results of coagulation tests and the method of post-tonsillectomy hemorrhage management were recorded. Results: The frequency of tonsillectomy was 19.2, 50.8, 18.6, 4, 2.1 and 5.3% in subjects aged 0-5, 5-10, 10-15, 15-20, 20-25 and more than 25 year old, respectively. The overall prevalence of post-tonsillectomy hemorrhage was 2.1%. The frequency of post-tonsillectomy hemorrhage was highest (13.6%) in patients aged 20-25 years. The incidence of post-tonsillectomy hemorrhage was zero in those aged ≤5 years. The rate of post-tonsillectomy hemorrhage was 54.5, 31.8 and 13.6% for those undergoing tonsillectomy, adenoidectomy and adenotonsillectomy, respectively. Secondary post-tonsillectomy hemorrhage (after 24 hours) was more common (81.8%). Moreover, the rate of re-admission for controlling the bleeding was 63.4% (14 cases). Conclusion: The incidence of post-tonsillectomy hemorrhage, the methods for its management and the need for re-admission are quite different in different age groups.